Importance of fairness in humanitarian relief distribution. Issue 14 (26th October 2018) - Anaya-Arenas, Ana María; Ruiz, Angel; Renaud, Jacques
Abstract: This article is inspired by some of the challenges faced by non-governmental organizations in the distribution of humanitarian relief to vulnerable rural communities. A major concern of these organizations is to warrant that relief is distributed in an impartial and transparent way, which gives rise to the notion of fairness. This article thus discusses the importance of fairness in relief distribution and how it can be defined, especially in a context where delivery of vital items must be ensured periodically. We also propose some performance indicators to measure fairness, which can be useful to organizations that are held accountable for the impartiality of their decisions. Finally, an empirical study of an academic case, inspired by a rural aid distribution problem, is used to analyse how different mathematical formulations may contribute in helping crisis managers integrate fairness or equity in their decisions.